Direct Oral Anticoagulants in the Prevention of Venous Thromboembolism Following Surgery for Hip Fracture in Older Adults: A Population-Based Cohort Study. (3rd January 2020) - Goh, En Lin; Gurung, Pratha Kumari; Ma, Shaocheng; Pilpel, Timothy; Dale, James Henderson; Kannan, Angela; Anand, Sambandam
Introduction: Direct oral anticoagulants (DOACs) decrease the risk of venous thromboembolism (VTE) without increasing the risk of hemorrhage in elective lower limb orthopedic surgery. However, the role of DOACs in preventing VTE following hip fracture surgery in the older adults remains unclear. This study aims to evaluate the efficacy and safety of DOACs in older adults undergoing surgery for hip fracture. Materials and methods: Single-center, retrospective, population-based cohort study of patients receiving either a DOAC or low-molecular-weight heparin (LMWH) for VTE prophylaxis following hip fracture surgery. Data obtained included patient demographics, comorbidities, fracture classification, time to surgery, procedure performed, and length of stay. Main outcomes assessed were incidence of VTE, incidence of major hemorrhage, and death within 30 days of surgery. Results: A total of 321 patients were included. Incidence of VTE was 0% in the DOAC group and 3.4% in the LMWH group (risk ratio [RR]:0.26, 95% confidence interval [CI]: 0.02-4.34, P = .35). Hemorrhage occurred in 7.4% and 3.0% of patients in the DOAC and LMWH groups, respectively (RR: 2.47, 95% CI: 0.77-7.91, P = .13). Mortality from VTE was 0% in the DOAC group and 0.7% in the LMWH group (RR: 0.97, 95% CI: 0.05-20.02, P = .99). Mortality from hemorrhage was 1.9% in the DOAC group and 0.7% in the LMWH group (RR: 2.47, 95% CI: 0.23-26.78, P = .46). Discussion: The use of DOACs for VTE prophylaxis following surgery in older adults with hip fracture was associated with a similar rate of VTE compared to LMWH. However, there was a worrying trend toward an increased risk of hemorrhage. Conclusion: In the present study of a carefully selected cohort of patients, the effect of DOACs in reducing the risk of VTE following surgery for hip fracture in the older adults was comparable to LMWH. However, a trend toward increased risk of hemorrhage was noted. Larger prospective studies will be required to identify patients who will benefit the most from treatment.